Emmanuel Levinas: Implications of the relational paradigm for bioethics (Revista Iberoamericana de Bioética, 2018)
In a changing world that offers new health-care situations, the inadequacy of traditional models of bioethics are demonstrated. A new ethic needs to be based more on a relational paradigm; where inter-subjectivity, encounters with ‘the Other’ particularly with his/her face as a unique person, and where responsibility is at the center, as outlined by Emmanuel Levinas, the French-Lithuanian philosopher. His philosophy helps bioethics in its search for foundations.
Keywords: The Other; care; responsibility; relationality